2004
DOI: 10.1029/2003jc001900
|View full text |Cite
|
Sign up to set email alerts
|

Suspended sediment and hydrodynamics above mildly sloped long wave ripples

Abstract: [1] We investigate the spatial and temporal distribution of suspended sediment and the associated hydrodynamics over mildly sloped long wave ripples on the inner shelf. These bedforms had wavelengths of approximately 1 m and heights of approximately 5 cm, in a mean water depth of 4 m. The vertical and temporal structures of the suspended sediment concentration (SSC) are consistent with the entrainment of sediment on the offshore flank of the ripple, and rapid vertical mixing at the time of flow reversal, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
(36 reference statements)
0
16
0
2
Order By: Relevance
“…Conventional models based on Reynolds-Averaged Navier-Stokes (RANS) equations (e.g., Chang and Hanes, 2004;Fredsøe et al, 1999) suffer from limitations such as requiring a priori knowledge of flow physics for model closures, low-order accuracy, and oversimplification of flow physics. Due to vastly improved computational capability in recent years, 3-D large-eddy simulations (LES) have successfully demonstrated the superiority over the RANS approach due to less assumptions involved in sub-grid closure (Henn and Sykes, 1999;Calhoun and Street, 2001;Chang and Scotti, 2003a,b;Barr et al, 2004;Yue et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional models based on Reynolds-Averaged Navier-Stokes (RANS) equations (e.g., Chang and Hanes, 2004;Fredsøe et al, 1999) suffer from limitations such as requiring a priori knowledge of flow physics for model closures, low-order accuracy, and oversimplification of flow physics. Due to vastly improved computational capability in recent years, 3-D large-eddy simulations (LES) have successfully demonstrated the superiority over the RANS approach due to less assumptions involved in sub-grid closure (Henn and Sykes, 1999;Calhoun and Street, 2001;Chang and Scotti, 2003a,b;Barr et al, 2004;Yue et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ripples were plotted in profile drawings and were determined to be important factors in defining the suspension of sediment grains. The ripples indicated that the energy of the waves was large enough to create chaotic turbulence fields at the beach slope (Chang and Hanes, 2004). In test series A and B, ripples did not affect offshore sediment yield because they were dampened by the incoming periodic waves, leaving a relatively flat bed.…”
Section: Resultsmentioning
confidence: 91%
“…Measurement of sediment transport using PC-ADP has a number of advantages relative to conventional measurements using OBS or ABS sensors paired with electromagnetic or acoustic current meters. Observations of c and u are co-located in the vertical and in the horizontal, and measurements are spatially integrated over a relatively large part of the horizontal plane (up to about 120 cm 2 in the present application) making them insensitive to sensor position relative to the ripple form and paths of ejected vortices (Chang and Hanes, 2004;Hurther and Thorne, 2011). On the other hand, there are also disadvantages with PC-ADP measurements.…”
Section: Discussionmentioning
confidence: 95%
“…Another disadvantage with conventional instrumentation is that transport magnitude is highly dependent on measurement position relative to a bedform, i.e. whether measurements are made in a ripple trough or at a ripple crest (Chang and Hanes, 2004;van der Werf et al, 2007). Hence, acoustic instruments that can remotely monitor fluid velocity and sediment concentration at identical positions relative to the bed with high vertical resolution within the wave boundary layer are best suited for quantifying transport under non-breaking waves over wave ripples in the field.…”
Section: Introductionmentioning
confidence: 99%